TCP/IP protocol suite - Forouzan, Behrouz A. (McGraw-Hill, 2010)
"TCP/IP Protocol Suite teaches students and professionals with no prior knowledge of TCP/IP everything they need to know about this highly technical subject while avoiding complex mathematical formulae. In order to accomplish this, Behrouz Forouzan uses an extensive collection of figures to demonstrate concepts so students can grasp them intuitively. Additionally, he provides many opportunities for students to check comprehension of ideas by completing the practice sets found at the end of each chapter.